For an Aesthetics of Sensations: intense body of Bartenieff Fundamentals and Body-Mind Centering - Patrícia de Lima (Revista Brasileira de Estudos da Presença, 2014)
This paper discusses concepts and methodological proposals that approach the theoretical and practical study concerning the body, understanding it as an expressive subject in constant mutation and process of reinvention.  For this reason, the study approximates two somatic approaches: Bartenieff Fundamentals™ and Body-Mind Centering™. The aim was to perceive how these somatic approaches allow the construction of an intensive body that engenders an aesthetics of sensations.